As estratégias pedagógicas para a leitura à primeira vista ao piano - Marcelo Almeida Sampaio (2017)
This research focus on teaching and learning strategies to develop piano sight-reading (SR) skills. The literature review on previous research and SR methods pointed that SR involves two central categories in order to solve many pedagogical problems: cognitive processing and motor behaviour. Specifically, this study tests the hypothesis that transposition is a more effective intervention than rhythm training and four-hands piano sight-reading repertoire. To verify this hypothesis, twenty-seven undergraduate students were randomized in one experimental and two control-groups in a pre-post-test after a SR training. The errors were scored in pitch, rhythm and hesitation. The individual errors were collected from three different tests in three graduated levels of difficulty in tonal repertoire (27 students x 3 tests x 3 levels), resulting in 243 scores (n=243). The students performances were recorded and statistically analysed by the Generalized Linear Models. The results showed that the students developed their sight-reading competences in 30%, although the interventions (transposition, rhythm training and four-hands repertoire) did not have any significantly effect on errors reduction (p=0,96). The research concludes that it is imperative to promote the training of the sight-reading specialist teacher. The data analysis revealed other findings: a) to practice bass clef reading, to practice more rhythm than pitch and to practice more left-hand than right-hand promotes SR significant development; b) isolated strategies had no effects in students scores; c) a hybrid approach with three or more predict variables seems to be the best way to develop a great competence in SR, as previous research in this area confirmed.